Traces of a backyard/studio: Encounters with the lines of the drawing (Revista Apotheke, 2025)
This article presents some traces left by cartographic drifts arising from encounters that took place in a backyard, which is understood as a studio space for both the artist and the teacher, one of the authors of this text. The writing resonates with the sensations experienced in that place, in contact with the earth and nature, bringing contemporary artistic practices with drawing, which create lines of connection with teaching and also with art and life. By exploring the events that insinuate themselves in the backyard/studio and the perception of their unforeseen events, the aim is to uncover possible developments for teaching with drawing, and not just about drawing. In this sense, teaching with drawing is understood as difference, with authors such as Gilles Deleuze and Félix Guattari, as well as Ana Godoy and Tim Ingold, respectively, with the meanings of drift and inhabitation. Through displacements as a field of experimentation, it enhances possible paths in which the creative processes involved in the poetic process of drawing also become a device for and in its teaching.
Keywords: drawing; teaching; experimentation; cartographic drift; backyard/studio